γ-Convergence of integral functionals and the variational dirichlet problem in variable domains - Kovalevskii, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
By using special local characteristics of domains Ω s ⊂Ω,s=12,..., we establish necessary and sufficient conditions for the γ-convergence of sequences of integral functionalsI λs :W k,m (Ω s )→ℝ, λ⊂Ω to interal functionals defined on W k,m (Ω).